Análises de meroterpenos produzidos por Penicillium brasilianum - Eugênio, Patrícia de Fátima Menegoci (2008)
This work describes the use of the high performance liquid cromatography (HPLC) technic coupled to the mass spectrometry technique for the analysis of fungal extracts, and the main purpose was the detection of meroterpens produced by P. Brasilianum. The fungal species P. Brasilianum was cultivated in a variety of artificial culture media: rice, wheat, maize, rice broth, solid decanted from rice broth and liquid medium Czapeck. In all the culture media tested the fungus presented a very good development, and also, the ions related to the meroterpens in study were detected in all the fungal extracts produced by these cultivations, except in Czapeck medium. The atmospheric pressure chemical ionization (APCI) was compared to the electrospray ionization, for the meroterpens analysis, and the result obtained was a great increase in detection power for this class of compounds, with the use of APCI. The P. brasilianum fungus was cultivated in Czapeck medium in the presence of Pinus taeda resin, alizarin, oleanolic, benzoic, salicylic, 2,5-dihydroxybenzoic, 2,6-dihydroxy-4-methyl-benzoic, 3,5-dinitrosalicylic, 3,5-dinitrobenzoic and ferulic acids, and 2 ,4 ,6 -trihydroxyacetophenone. The presence of these exogenous aditives modified the fungal metabolic profile, because the cromatographic profiles of the extracts produced showed a differentiation, in comparation to the fungal extract without aditive. Only the fungal extract produced in the presence of ferulic acid presented the meroterpens PSP-3 and PSP-8. The fungal extracts produced without any aditive also did not present meroterpens.